Gender inclusiveness in student learning materials: Study of elementary school context in Indonesia - Salsabila, Indri; Hasanah, Anisa Rohmah; Mutakin, Hendriyan Ihsan; Lestari, Triana (Universitas Negeri Yogyakarta, 2024)
This study intends to evaluate the gender inclusivity in learning and education research field's growth trend from 2013 to 2023. The steps of the research are as follows: (i) assembling the tools and materials; (ii) organizing meetings; (iii) screening; (iv) visualizing; and (v) reviewing the data and outcomes that have been published. There were 988 articles in the keyword search results for